Modified recycled paper-based adsorbent for nickel removal - Awang, N. A. (2020)
The outcome from the industrialization and urbanization promotes the environmental problems especially related to the release of heavy metals. The adsorption method is a promising technique among all the available approaches in heavy metal removal treatment due to its high efficiency, low cost, and simplicity in design and operation. A good selection of solid sorbent becomes one of the greatest problems in adsorption technique. In this present work, we developed recycled paper-based cellulose adsorbent grafted with acrylonitrile in the presence of ceric ammonium nitrate as the initiator. The modified adsorbent was used to adsorb Ni(II) from the aqueous solution. The adsorption process was conducted at different operational conditions by varying the pH of the solution, initial concentration of the Ni(II), and the contact time for the adsorption to reach equilibrium and obtained the highest adsorption capacity. The result demonstrated that the grafted recycled paper-based cellulose adsorbent had improved the adsorption capacity of Ni(II) ions. The most propitious condition obtained was at pH 5 after 1 h, with an initial concentration of 160 mg/L of Ni(II) ions; the removal reached 317.5 mg/g (79.3% removal). The surface studies of the adsorbent before and after Ni(II) ions adsorption was analyzed by using the scanning electron microscopy (SEM). The adsorption equilibrium data of Ni(II) ions was best described by the Freundlich and Pseudo-second-order model. Conclusively, the prepared grafted recycled paper-based cellulose adsorbent proved to be competitive and a promising adsorbent for the removal of Ni(II) ion from aqueous solution, as well as in wastewater treatment application.